Calcium flickers steer cell migration - Cheng, Heping (Henry Stewart Talks, 2012)
Paradox of calcium signaling in cell migration, Calcium flickers in migrating fibroblasts, Trigger mechanism and molecular origin of calcium flickers, Calcium flickers steer cell turning, Feedback loop between calcium flickers and cytoskeletal traction force generation, Role of calcium flickers in chemotaxis, Calcium flicker model of cell turning
Archived at 2020/08/13